Kajian Teori dan Pandangan Alkitab Terhadap Kepemimpinan Karismatik - Adi Suhenra Sigiro; Putri Yulia Citra Br. Berutu; Berlina Simatupang; Fritcen Vanny M Pardede (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2025)
Leadership plays a crucial role in organizational effectiveness, especially in creating work synergy, building motivation, and facing the challenges of change. This article discusses in depth the type of charismatic leadership that has a strong personal appeal and influence on followers. Through the method of literature study and descriptive approach, this article explores the basic concept of charismatic leadership, its benefits, advantages, and disadvantages. Charismatic leaders are able to build strong emotional relationships, increase loyalty, and create an innovative work environment. However, this leadership style also carries risks, such as excessive dependence on the leader and the potential for a cult of personality. Charismatic leadership is biblical leadership.